Successful long-term mandibular reconstruction and rehabilitation using non-vascularised autologous bone graft and recombinant human BMP-7 with subsequent endosseous implant in a patient with bisphosphonate-related osteonecrosis of the jaw. Issue 9 (November 2015) - Rahim, Ishrat; Salt, Stephen; Heliotis, Manolis
Abstract: We describe a case of extensive osteonecrosis of the mandible after a dental extraction in a 71-year-old woman who was taking alendronic acid (Fosamax ®, Merck) for osteoporosis. Bone damaged by bisphosphonate-related osteonecrosis of the jaw (BRONJ), also now known as medication-related osteonecrosis of the jaw (MRONJ), can be regenerated and filled with endosseous implants using non-vascularised autologous grafts.